Democratic Civility and the Dangers of Niceness. Issue 2 (17th February 2017) - Ward, Ian
Abstract : Contemporary debates about the virtue of civility oscillate between anxious calls for more of it in contemporary politics, as a panacea for all manner of religious-political conflict, and wholesale debunkings of civility talk, as an ideological fog intended to induce conformity to the terms of unjust social arrangements. I argue that this oscillation should come as no surprise, given the term's fraught theological and political associations in the history of modern ethical thought. This history left civility with an ambivalent legacy, one associated with democratic respect on the one hand, and hypocrisy and deception, on the other. Through a reading of Martin Luther King Jr.'s "Letter from Birmingham Jail, " I try to rescue civility from this oscillation, by explicating it as an ancillary virtue: the part of justice that disposes citizens to confront unjust relationships in ways that leave open the possibility of relational repair. When explicated with due care and set in an interactive context of other virtues – including courage, prudence and toleration – civility can be distinguished from its semblance, niceness. This distinction helps us understand civility, properly understood, as neither a cure-all for democratic conflict nor an ideological device of conflict suppression, but rather as an ancillary, but important, excellence of character helping to sustain democratic relationships of mutual recognition.